Perception and Motivation Study as a Determinants of Ecotourism Development in Tanah Datar Region - Adam Rachmatullah; Ricky Avenzora; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
During the last decade, many countries are paying special concern to develop of tourism and ecotourism industry cause able to accelerate development in a region. This research aims to analyze stakeholder perceptions and motivation determinants, a long with to formulate ecotourism development strategy. The research method used in closed ended questionnaire instrument and then data were analyzed by using one score one criteria scoring system. The result of the study showed that a local community and government perceptions have as a conclusion is a good or stil the positive sphere so that it is feasible to be develop as all forms of ecotourism. Afterwards, the result of motivations data showed that stakeholders have a high interest (score 6-7) to be actively involved in any form of ecotourism development. In order to realize the integrated ecotourism development in Tanah Datar Region, then some important things that need to be optimized, among others: 1) regional development perspective; 2) social-culture perspective; 3) capacity building perspective; 4) marketing perspective. Keywords: ecotourism, motivation, perception, Tanah Datar Region